Lower-limb stiffness mediates speed but not turning angle during unplanned side-step cutting. (22nd January 2021) - Liew, Bernard X.W.; Sullivan, Laura; Morris, Susan; Netto, Kevin
Abstract: An inability to pre-plan a side-step cutting maneuver results in a greater reduction in speed and shallower cut angle. Although leg stiffness has not been directly quantified in cutting, indirect evidence suggest that greater stiffness may benefit cutting speed, but lower stiffness may benefit cut angle. No studies have investigated if stiffness causally mediates the relationship between anticipation, cutting speed and angle. The aims of the present study were to determine the influence of anticipatory cues on leg stiffness, and quantify the mediation effects of stiffness on cutting speed and angle. Seventeen healthy participants performed a 45° cut at an approach speed of 4 m/s. Leg stiffness (% bodyweight/leg length [BW/LL]), cutting angle and change in running speed between initial contact and toe-off of the cut were calculated. Causal mediation analysis was performed with anticipatory cues as the independent variable, cutting speed and angle as the dependent variables, and stiffness as the mediator. Unanticipated cutting significantly increased leg stiffness ( β = 3.82 % B W / L L, P = 0.005 ) compared to anticipated cutting. The average causal mediation effect of stiffness on cutting angle was not significant (P = 0.68). The average causal mediation effect of stiffness on cutting speed was significant (−0.02 m/s [95%CI −0.04 to 0.00 m/s, P = 0.016). Reduced preplanning time in cutting increased leg stiffness. Alterations in leg stiffness only explained the change in speed, and not angle, associated with cutting under different anticipatory cues. Loss of speed when cutting is unplanned may be mitigated by improving leg stiffness.